Mesoporous and Nanostructured TiO2 layer with Ultra-High Loading on Nitrogen-Doped Carbon Foams as Flexible and Free-Standing Electrodes for Lithium-Ion Batteries - Chu, S.; Zhong, Y.; Cai, R.; Zhang, Z.; Wei, S.; Shao, Zongping (Wiley, 2016)
A simple and green method is developed for the preparation of nanostructured TiO2 supported on nitrogen-doped carbon foams (NCFs) as a free-standing and flexible electrode for lithium-ion batteries (LIBs), in which the TiO2 with 2.5–4 times higher loading than the conventional TiO2-based flexible electrodes acts as the active material. In addition, the NCFs act as a flexible substrate and efficient conductive networks. The nanocrystalline TiO2 with a uniform size of ≈10 nm form a mesoporous layer covering the wall of the carbon foam. When used directly as a flexible electrode in a LIB, a capacity of 188 mA h g−1 is achieved at a current density of 200 mA g−1 for a potential window of 1.0–3.0 V, and a specific capacity of 149 mA h g−1 after 100 cycles at a current density of 1000 mA g−1 is maintained. The highly conductive NCF and flexible network, the mesoporous structure and nanocrystalline size of the TiO2 phase, the firm adhesion of TiO2 over the wall of the NCFs, the small volume change in the TiO2 during the charge/discharge processes, and the high cut-off potential contribute to the excellent capacity, rate capability, and cycling stability of the TiO2/NCFs flexible electrode.